El síndrome de Burnout y su relación con los rasgos de personalidad en el personal de salud que asiste a pacientes oncológicos residentes en el Instituto contra el cáncer Solca de la ciudad de Loja periodo febrero-julio del 2013 - Toledo Tacuri, Juan Andrés (2014)
Burnout syndrome is a disorder that is caused by the constant emotional, social and work pressures in a person. The most affected with this syndrome are professional doctors and other health workers especially by constant schedule changes and get involved in the problems of patients. This research work correlational quantitative and is aimed at determining whether personality traits act as facilitators or protective factors in the development of burnout syndrome. We worked with 65 health professionals Cancer Institute "SOLCA". The research results known to us the presence of burnout syndrome in 14% of health professionals. Health professionals Anankastic Personality traits have high levels of emotional exhaustion , depersonalization ( 14%) and Low Performing Personal (4% ) giving us the pattern of the characteristics of this personality trait may facilitate the development of burnout syndrome. Similarly professionals with Histrionic Personality Traits mostly demonstrate high levels of personal accomplishment (29 %), which shows that the characteristics of this personality trait act as protective factors in the development of burnout syndrome. The contribution of this research is a psychotherapeutic plan, which will have four stages, which treat important topics about Burnout Syndrome, offering staff health techniques and tools for the proper management and control of the syndrome. KEYWORDS: Burnout, Personality, Personal Health, job stress, emotional exhaustion.